Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1111/opn.12373
|View full text |Cite
|
Sign up to set email alerts
|

A learning process towards person‐centred care: A second‐year follow‐up of guideline implementation

Abstract: Background Research claims that ‘learning by doing’ creates new thinking, often leading to new practice. Objectives The aim was to explore and describe the staff learning process from the first to the second year when adopting person‐centred care into clinical practice in a nursing home for persons with dementia. Method The data consisted of poster texts from staff and written notes by researchers obtained from the group discussions. The study involved 24 care units (200 staff). Content analysis was chosen as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Understanding the specific characteristics of this process and individuals’ unique needs for information can provide HCPs with essential insight. This can enhance understanding for health information needs while safeguarding PCC in daily practice [ 26 , 27 ]. HL is a concept seen as a health asset that encompasses crucial dimensions, each of which requires specific cognitive skills and depends on the quality of the information provided [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Understanding the specific characteristics of this process and individuals’ unique needs for information can provide HCPs with essential insight. This can enhance understanding for health information needs while safeguarding PCC in daily practice [ 26 , 27 ]. HL is a concept seen as a health asset that encompasses crucial dimensions, each of which requires specific cognitive skills and depends on the quality of the information provided [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Understanding the speci c characteristics of this process and women's unique needs for information can provide HCPs with essential insight. This can enhance understanding for the women's health information needs while safeguarding PCC in daily practice (26,27). HL is a concept seen as a health asset that encompasses crucial dimensions, each of which requires speci c cognitive skills and depends on the quality of the information provided (28).…”
Section: Introductionmentioning
confidence: 99%
“…Implementation of evidence into practice is still a field in development and warrants further exploration (Kindblom et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, a systematic review found that no one single strategy, or combination of strategies, can be linked directly to successful implementation of nursing guidelines (Spoon et al, 2020). Implementation of evidence into practice is still a field in development and warrants further exploration (Kindblom et al, 2021).…”
Section: Introductionmentioning
confidence: 99%